A Professional Development Model Enhancing Teacher Leadership Practices in Private Universities in Western District, Yangon, Myanmar - Ko Ko, Khin Phone Kyaw; Mhunpiew, Nathara; Thaima, Waraporn (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
Acknowledging the pivotal role of teachers in shaping institutional success and educational outcomes, this study aims to develop a professional development model that enhances teacher leadership practices in private universities in Western District, Yangon, Myanmar. The study was conducted in twelve private universities in Western District, Yangon, with a sample size of 196 teachers, including part-time and full-time faculty. The research employed both qualitative and quantitative approaches. Systematic reviews of literature sources informed the creation of survey questionnaires. These questionnaires were then used to analyse the needs assessments of teachers. Through a qualitative approach, seven teacher leadership practices were analysed: setting direction, developing people, redesigning the organisation, transformational leadership, participative leadership, distributed leadership and instructional leadership and they were validated with 5 experts. The analysis of the questionnaires revealed that teachers’ highest priority needs were (1) redesigning the organisation, (2) instructional leadership, (3) developing people, (4) setting direction, (5) participative leadership, (6) distributed leadership and (7) transformational leadership. Subsequently, a Professional Development Model was developed based on these findings. The model was validated by 15 experts from the higher education sector. The study concludes with recommendations for expanding the professional development model and discussing implications for policy and practice in Myanmar’s private university context. Recognizing teacher leadership’s role in driving innovation, this professional development model holds significant potential for elevating educational standards and improving student outcomes within Myanmar’s private universities.